Patterns and stability of food preferences among a national representative sample of young, middle-aged, and elderly adults in China: A latent transition analysis. (December 2021) - Ma, Zhuanzhuan; He, Jinbo; Sun, Shaojing; Lu, Tom
Highlights: Latent class analysis revealed three types of food preferences for Chinese adults. Multiple demographic variables (e.g., gender) were related to Chinese adults' food preference patterns. Latent transition analysis showed the pattern of preference for fruits and vegetables were most stable. Abstract: The purpose of this study was to explore the patterns and stability of, as well as the predictors for, Chinese adults' food preferences. With the panel data set derived from the China Health and Nutrition Survey (CHNS), latent class analysis (LCA) and latent transition analysis (LTA) were employed to analyze the data of 8850 adults aged 18–40 years (young), 41–60 years (middle-aged) and 61 years above (elderly) over a 4-year period (year 2011 as baseline and year 2015 as follow-up). Latent class analysis revealed three types of food preferences: preference for fruits and vegetables, preference for a varied diet and low food preference . Gender, dietary knowledge, residence, education, and BMI were revealed as significant predictors of the class memberships. From baseline to follow-up, the most stable status in young adult group was preference for fruits and vegetables as it had a high transition probability 0.764 of remaining in the same class. While low food preference and preference for a varied diet statuses were unstable, they had transition probabilities of 0.590 and 0.554, respectively, moving to the preference for fruits and vegetables in year 2015. For middle-aged and elderly groups, the most stable and unstable statuses were preference for fruits and vegetables and preference for a varied diet, respectively. The unstable classes all had over 50% probability of moving to the preference for fruits and vegetables after four years. Potential explanations and implications are also discussed.